Healthcare resource utilization and costs of major atherothrombotic vascular events among patients with peripheral artery disease after revascularization. (1st January 2021) - Desai, Urvi; Kharat, Akshay; Hess, Connie N.; Milentijevic, Dejan; Laliberté, François; Zuckerman, Peter; Benson, John; Lefebvre, Patrick; Hiatt, William R.; Bonaca, Marc P.
Abstract: Aims: Peripheral artery disease (PAD), often treated with lower extremity revascularization, is associated with risk of major atherothrombotic vascular events (acute limb ischemia [ALI], major non-traumatic lower-limb amputation, myocardial infarction [MI], ischemic stroke, cardiovascular death). This study aims to assess healthcare resource utilization and costs of such events among patients with PAD after revascularization. Materials and methods: Patients aged ≥50 years with PAD who were treated with lower-extremity revascularization were identified from Optum Clinformatics Data Mart claims database (01/2014–06/2019). The first lower extremity revascularization after PAD diagnosis was defined as the index date. Patients had ≥6 months of health plan enrollment before the index date. Patients were followed until the earliest of 1) end of enrollment or data; 2) diagnosis of atrial fibrillation or venous thromboembolism; or 3) oral anticoagulant use. All-cause healthcare resource use per-patient-year was compared before and after a major atherothrombotic vascular event post-revascularization among those with an event. Additionally, event-related healthcare costs per-patient-year were reported for each event type. Results: Of the 38, 439 PAD patients meeting the study criteria, 6, 675 (17.4%) had a major atherothrombotic vascular event. On average, patients were observed for 7.3 months before an event and 6.2 months after an event. Patients with an event had significantly higher all-cause healthcare resource use versus similar metrics pre-event (e.g. inpatient visits among those with ALI: 3.5 ± 5.8 post-event vs. 2.0 ± 8.1 pre-event, p < .05). Event-related costs ranged from 57, 825±131, 810 per-patient-year for ischemic stroke to 108, 302±150, 168 for major non-traumatic lower-limb amputation. Limitations: Data do not contain clinical information. Additionally, results are limited to commercially insured and Medicare Advantage beneficiaries. Conclusion: Patients with PAD who experience major atherothrombotic vascular events post-revascularization have considerably higher healthcare resource use and costs compared with similar metrics pre-event. Therefore, reducing the rate of such events could reduce overall healthcare costs for this population.